2010
DOI: 10.1007/s10875-010-9486-2
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Lupus Phenotype by Adiponectin Deficiency in Autoimmune Mouse Models

Abstract: Adiponectin is an adipocyte-derived cytokine with anti-inflammatory properties. Paradoxically, circulating adiponectin levels are increased in a number of inflammatory diseases. Thus, we sought to define the role of adiponectin deficiency in mouse models of autoimmunity. Adiponectin-deficient mice on a C57BL/6 background do not develop an autoimmune phenotype. Autoimmunity was also not observed in adiponectin-deficient mice generated on the permissive MRL background. However, adiponectin deficiency exacerbated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…This bridging mechanism is also shared with C1q [reviewed in (3)]. In addition, adiponectin deficiency, similar to C1q deficiency, accelerates the onset and severity of the autoimmune phenotype observed in autoimmune susceptible murine strains (13, 40). Herein, we provide evidence demonstrating that in addition to acting as bridging molecules to enhance efferocytosis via calreticulin/LRP (32), both C1q and adiponectin enhance efferocytosis by upregulating Mer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This bridging mechanism is also shared with C1q [reviewed in (3)]. In addition, adiponectin deficiency, similar to C1q deficiency, accelerates the onset and severity of the autoimmune phenotype observed in autoimmune susceptible murine strains (13, 40). Herein, we provide evidence demonstrating that in addition to acting as bridging molecules to enhance efferocytosis via calreticulin/LRP (32), both C1q and adiponectin enhance efferocytosis by upregulating Mer.…”
Section: Discussionmentioning
confidence: 99%
“…C1q is structurally more similar to adiponectin when compared to collectins, such as MBL, based on homology in the globular head region. Moreover recent data suggest shared functions for C1q and adiponectin in innate immunity, since similar to C1q-deficiency, deficiency in adiponectin is associated with defective efferocytosis and development of autoimmunity (13, 14). …”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that adiponectin acts as a negative modulator of the autoimmune phenotype in a murine model of lupus, and this effect is more pronounced in female versus male mice (108). It was also reported that mice with lupus that lack adiponectin develop more severe disease than wild-type mice, which suggested that adiponectin is involved in regulating disease activity (109).…”
Section: Adiponectin and Rheumatic Diseasesmentioning
confidence: 99%
“…Adiponectin has also been found to be increased in ankylosing spondylitis, type I diabetes, and ulcerative colitis [88][89][90][91]. In mouse lupus models of SLE, decreased adiponectin is associated with increased renal damage [92,93]. Conversely, in SLE patients, multiple reports have demonstrated increased levels of adiponectin in patients' serum, although there is little indication that this is associated with disease activity [63,94,95].…”
Section: Adiponectinmentioning
confidence: 99%